PERLINDUNGAN HUKUM TERHADAP SUAMI SEBAGAI KORBAN KEKERASAN DALAM RUMAH TANGGA YANG DILAKUKAN OLEH ISTRI - Prambudi Adi Negoro dan Ratna Kusuma Hadi, Gilang Kusuma Hadi (GEMA, 2015)
This research is a normative and prescriptive law research, determining in concreto law through case study approach and constitution approach. The data used in this research is secondary data which extracted from primary and secondary law materials. Data gathering technique used in this research is literature study. The analysis in this research is conducted through drawing conclusion from general matters which include various verdict on legal forms on husbands who happen to be domestic violence victims committed by their wives. deductive syllogism is conducted in order to answer the research question that appears. Based on the research conducted, it can be concluded that the legal forms given to the husbands who happen to be domestic violence victims based on Act No.23 year 2004 on the Abolition of Domestic Violence, Act No. 31 year 2014 on the Revision of Act No.13 year 2006 on Victim and Witness Protection and Government Regulation No. 04 year 2006 on Recovery of Domestic Violence Victim, husbands who happen to be victim of domestic violence have rights to get protection from families, police, judiciary, courts, advocates, social institution or other institutions, either for temporary or based on verdict issued by courts.